Addiction, cigarette smoking, and voluntary control of action: Do cigarette smokers lose their free will?. (June 2017) - Baumeister, Roy F.
Abstract: Opinions differ widely as to whether addicts lose the ability to control their behavior and employ free will. This article reviews empirical findings regarding multiple questions relevant to the issue of free will among addicted smokers: Is smoking voluntary behavior? Can people quit smoking? Why don't people quit smoking? Why do smokers relapse when they try to quit? Do addicted smokers suffer from irresistible cravings? Are there some people who cannot quit? Are there conditions that make resistance impossible? Why would they smoke knowing it can kill them? The evidence reviewed here seems most consistent with the view that smokers retain control over their actions but cannot easily stop having frequent desires to smoke. Highlights: By most criteria and measures, smokers retain free will to control their actions, though they lose control over desires and motivations. Smoking even by addicts retains many signs of voluntary behavior. Smokers seem generally able to abstain and quit. Addictive smoking may resemble a habit that will run off as normal (i.e., smoking) unless specifically and effortfully countered.